Effect of Integrated Teaching versus Conventional Lecturing on MBBS Phase I Students - Dandannavar*, Vijaya.S. (Recent Research in Science and Technology, 2010)
Advances in scientific knowledge and innovations in educational field that necessitates constant change in medical school curricula. At present in ourÂ  Institution the existing system of undergraduate curriculum for MBBS I phase is non integrated, discipline based where in teaching involves only didacticÂ  lectures, fully teacher centered process, tutorials and to a lesser extent with group discussion. Each subject has its own block of time usually restricted to one part of the course. Therefore there are many flaws in present teaching system. Students are passive learners, no exposure to critical thinking, no active learning, difficulty in co relating all three preclinical subjects and apply this knowledge & transfer this information into clinical practice. To improve quality of the students and to have effective diagnosis, for better treatment of the patients. Integrated teaching is the need of the hour, and students learn better when engaged by different materials of learning. This alternative method of teaching would be beneficial to the student community at the institution and would be an ideal approach. Students will learn in context of medical problem integrating all three basic science subjects, understand and correlate basis of clinical problem and will enhance clinical learning.